Quantifying the burden of premature mortality at national level in France in 2016. (20th October 2021) - Haneef, R; Constantinou, P; Rachas, A; Ghosn, W; Kudjawu, Y; Grave, C; Torres, M; Fayad, M; Ung, A; Bonaldi, C
Abstract: Background: Efforts to accurately measure premature mortality are important to monitor the impact of diseases and injuries on population health and to set policy priorities. This is an ongoing study with a strong collaboration between Santé Publique France and the French National Health Insurance, whose main objective is to provide the first national estimates of Years of Life Lost (YLLs) for all causes of death in France. Methods: The French national health data system (SNDS) contains detailed nationwide causes of death data, reported using ICD-10 codes. We used the underlying cause, as defined by the Center for Epidemiology on Medical Causes of deaths, of all deaths for year 2016 (the last year available). For this preliminary study without redistribution of ill-defined deaths (IDDs), national sex-specific life expectancy tables were used to estimate YLLs by age class, sex, and cause of death categories at national level. We identified and quantified IDDs and also compared YLLs to crude mortality. Results: In 2016, we estimated approximately 7.3 million YLLs (586, 519 registered deaths), of which 35.1% were due to neoplasms, 17.8% to cardiovascular diseases (respectively 34.5% and 17.3% in men; 35.8% and 18.4% in women) and 10.3% to injuries (4.9% among people aged 65 or more at time of death; 34.5% among people aged 25-44). Approximately 27% of the deaths registered were IDDs, representing approximately 1.8 million YLLs. Conclusions: These preliminary results confirm the importance of YLLs as a metric to target preventive strategies according to age. Moreover, by quantifying IDDs, we highlight that data gaps are important even in settings with highly developed health information systems. Next steps include applying an IDD redistribution methodology, aspirational life table and computing subnational YLLs. The French collaborative initiative should address those gaps and propose national and subnational burden metrics in the following months. Key messages: Methodological and data requirements to compute YLLs constitute a challenge even in settings with developed health information systems, highlighting the need of national institutional collaborations. Highlight data gaps in terms of ill-defined deaths in mortality database.